In vitro and in vivo efficacy of green synthesized AgNPs against Gram negative and Gram positive bacterial pathogens. (January 2022) - Sheng, Yequan; Narayanan, Mathiyazhagan; Basha, Sakeenabi; Elfasakhany, Ashraf; Brindhadevi, Kathirvel; Xia, Changlei; Pugazhendhi, Arivalagan
Graphical abstract: Highlights: Ruellia tuberosa mediated AgNPs against Gram negative and Gram positive pathogens was tested. RT-AgNPs showed antibacterial and antibiofilm activity against S. aureus and P. aeruginosa. RT-AgNPs showed antagonistic (Vancomycin) and additive (Gentamicin) against P. aeruginosa. RT-AgNPs inhibited more than 50 % of Pyocyanin in P. aeruginosa. RT-AgNPs showed non haemolytic activity against Human Red blood Cells. Abstract: Global threat of mortality and morbidity increasing due to pathogenic bacterial infection and disease become a significant concern for human population. Development of multidrug resistant bacterial pathogens has increased the search of alternative to conventional antibiotics and small molecules. Metallic nanoparticles are rapidly growing in the field of biomedicine, bioremediation, and bioengineering. Metallic nanoparticles synthesized using plant extract gives an upper edge against toxicity and efficacy of the materials. Silver and silver salt is practised in health organization around the world for killing bacterial pathogens. The present study, one-pot synthesized Rubella tuberosa mediated silver nanoparticles (RT-AgNPs) for the inhibition of ESKAPE panel of bacterial pathogens especially Staphylococcus aureus and Pseudomonas aeruginosa . The Minimal Inhibitory Concentration (MIC) of RT-AgNPs was determined as 4 μg/mL against both pathogens, while the Biofilm Inhibitory concentration (BIC) was determined as 4 μg/mL and 16 μg/mL against Gram negative ( P. aeruginosa ) and Gram positive ( S. aureus ) pathogens. The synergy of RT-AgNPs with conventional antibiotics showed the better efficacy with Vancomycin and Gentamicin against S. aureus and P. aeruginosa respectively. Further haemolytic activity of RT-AgNPs against human red blood cell confirmed the non-toxicity at the higher concentration of 64 μg/mL. Thus, RT-AgNPs prove to be suitable candidate for the inhibition of biofilm and pathogenicity of Gram negative and Gram positive pathogens.